Bio Chemical Analysis of Infected and Non Infected Leaf Galls of Tirunelveli District, Tamil Nadu - Sundari, M. S.; Benniamin, A.; Beschi Antony Rayan, S. (Indian Forester, 2011)
The biochemical parameter such as pigment content including Chlorphyll a, Chlorophyll b, total Chlorophyll, sugar, protein, amino acid and phenol of healthy and infected leaves were analyzed. Among the content of the pigment, sugar of the gall tissue was found to be more in all the three plants and protein was found decreased in the gall tissue; other contents were found increased.